The Effect of Commissioners Board Size and Committee Board Size on Disclosure of Corporate Social Responsibility (CSR) - Hafidzi, Achmad Hasan (Universitas Muhammadiyah Prof. DR HAMKA., 2019)
This study aims to analyze the effect of board size and committees size to corporate social responsibilitythrough financial performance. The sample used in this study is secondary data of companies listed LQ-45 Index in 2013-2017 and determined using a purposive sampling method. The data about researchvariables are available in the financial report. The data analysis method is using path analysis. Theresults were showed that the size of commissioners board to corporate social responsibility was significantpositive, size of committees to corporate social responsibility was significant positive relationship, size ofcommissioners board to financial performance was significant positive relationship, size of committeesto financial performance was relationship positive significant, financial performance to corporate socialresponsibility shows a significant positive relationship.